FINITE ELEMENT MODELING OF LAPAN-A5/CHIBASAT DEPLOYABLE SOLAR PANEL COMPOSITE PLATE - Triharjjanto, Robertus Heru; Budiantoro, Poki Agung (BRIN Publishing, 2018)
LAPAN-A5/ChibaSat, that will carry synthetic aperture radar payload, requires a lot more power generation capacity, compared to its predecessor. Therefore, its solar panel will be deployed in orbit to ensure maximum sun exposure. Since the deployable system requires solar panel plate that lightweight and strong, honeycomb composite material is selected. The selection of such material requires special treatment in the satellite structural stiffness calculation. The objective of the research is to find simple stiffness model of the plate, so that later it can be integrated with the total satellite structural model and used by launch authority in its total vehicle modal analysis. The modeling used finite element software, and the simplified honeycomb model is validated using standar plate stiffnes problem. After model validation, the boundary condition as in the LAPAN-A5/ChibaSat deployable system is imposed. The result shows that the stiffness of the deployable solar panel plate has met the launch requirement of PSLVâ€™s auxiliary payload. Therefore, the design mode can be used in the development of LAPAN-A5/ChibaSat. Â